2022
DOI: 10.1021/acs.est.2c02906
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Advanced Oxidation of Perfluorooctanoic Acid: Mechanisms and Process Optimization with Kinetic Modeling

Abstract: Electrochemical advanced oxidation processes (EAOPs) are promising technologies for perfluorooctanoic acid (PFOA) degradation, but the mechanisms and preferred pathways for PFOA mineralization remain unknown. Herein, we proposed a plausible primary pathway for electrochemical PFOA mineralization using density functional theory (DFT) simulations and experiments. We neglected the unique effects of the anode surface and treated anodes as electron sinks only to acquire a general pathway. This was the essential fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…The specific structures of different PFAS and Ti 4 O 7 crystals, transition states of PFAS transformation, and the degradation pathways can be calculated by DFT. , For instance, DFT is applied to evaluate the thermodynamic preference of possible elementary steps of the overall PFAS degradation. The calculated adsorption energy of PFAS and transition states of these elementary steps coordinate well with the experimental results, which can guide the rational design of the Ti 4 O 7 IEM structure and components. , In addition, the operation conditions of the Ti 4 O 7 IEM including current density and flux can be adjusted to improve the PFAS degradation performance. , Relevant mathematic models revealed that the mass transfer rate and electric energy consumption escalate along with the flux across the Ti 4 O 7 IEM.…”
Section: Ti4o7 Iemssupporting
confidence: 57%
See 1 more Smart Citation
“…The specific structures of different PFAS and Ti 4 O 7 crystals, transition states of PFAS transformation, and the degradation pathways can be calculated by DFT. , For instance, DFT is applied to evaluate the thermodynamic preference of possible elementary steps of the overall PFAS degradation. The calculated adsorption energy of PFAS and transition states of these elementary steps coordinate well with the experimental results, which can guide the rational design of the Ti 4 O 7 IEM structure and components. , In addition, the operation conditions of the Ti 4 O 7 IEM including current density and flux can be adjusted to improve the PFAS degradation performance. , Relevant mathematic models revealed that the mass transfer rate and electric energy consumption escalate along with the flux across the Ti 4 O 7 IEM.…”
Section: Ti4o7 Iemssupporting
confidence: 57%
“…The calculated adsorption energy of PFAS and transition states of these elementary steps coordinate well with the experimental results, which can guide the rational design of the Ti 4 O 7 IEM structure and components. 55,56 In addition, the operation conditions of the Ti 4 O 7 IEM including current density and flux can be adjusted to improve the PFAS degradation performance. 53,57 Relevant mathematic models revealed that the mass transfer rate and electric energy consumption escalate along with the flux across the Ti 4 O 7 IEM.…”
Section: Pfas Degradation Using Ti 4 O 7 Iemsmentioning
confidence: 99%
“…To examine the effect of surface termination of MXenes on PFCA degradation, we calculated the free energies of different possible intermediates according to a reported degradation pathway for PFOA over three models (Ti 3 C 2 Cl 2 , Ti 3 C 2 F 2 , and Ti 3 C 2 O 2 ) . The overall pathways are shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1a To examine the effect of surface termination of MXenes on PFCA degradation, we calculated the free energies of different possible intermediates according to a reported degradation pathway for PFOA over three models (Ti 3 C 2 Cl 2 , Ti 3 C 2 F 2 , and Ti 3 C 2 O 2 ). 49 The overall pathways are shown in Figure 1b. First, in this degradation pathway, deprotonated PFOA (C 7 F 15 COO − ) exhibited the strongest adsorption energy on • radical and COF 2 ; COF 2 could rapidly react with water to finally form CO 2 and HF.…”
Section: Understanding the Interactions Between Pfasmentioning
confidence: 99%
“…Several technologies have been developed to degrade PFASs, including high-temperature pyrolysis, electrochemical oxidation (EO), UV photooxidation, UV photoreduction, and ultrasonic irradiation . Among these technologies, EO technology has been proven to be an efficient method to degrade PFASs. , A great deal of research has focused on developing EO anode materials with excellent performance, such as boron/nitrogen B/N codoped diamond, Ti/SnO 2 –Sb-Bi, Ti/SnO 2 –Sb/PbO 2 , and Magnéli phase Ti 4 O 7 , , for degrading PFASs. Nevertheless, the roles of the various oxidative free radicals generated by electrochemical systems lack detailed evaluation.…”
Section: Introductionmentioning
confidence: 99%